Optimization of water infrastructure design and management in multi-use river basins under a changing climate - Hunu, Kenneth D., author; Conrad, Steven A., advisor; DePue, Michael, committee member; Grigg, Neil, committee member; Bradley, Thomas, committee member; Sharvelle, Sybil, committee member (Colorado State University. Libraries, 2024)
Traditional approaches to the hydrologic design of water infrastructure assume that the climate is stationary, and that historical data reflect future conditions. The earth's climate is not stationary but changing with time. The traditional approach may, therefore, no longer be applicable. In addition to the issue of nonstationarity of climate, the design of water infrastructure to meet a particular need, such as water supply, is often assumed to be a single-objective optimization problem and is done without consideration of other competing watershed uses and constraints such as recreation, hydropower generation, environmental flows, and flood control. Such an approach routinely fails to adequately address the challenges of complex systems such as multi-use river basins that require an understanding of the linkages between the various uses and stakeholders. Water infrastructure design will benefit from a holistic and systems engineering approach that maximizes the value to all users while serving its primary function. The objective of this research was to identify and develop a new approach for designing and managing water infrastructure in multi-use basins that accounts for the effects of climate change by shifting the current static design paradigm to a more dynamic paradigm and accounts for other multi-use basin objectives, which may include recreation, hydropower generation, flood control, environmental flows, and water supply. This research involved an extensive literature review, exploration of concepts to solve the identified problems, data collection, and development of a decision support research tool that is formulated such that it can be used to test the viability of various hypotheses. This dissertation presents a practical approach for designing and managing water infrastructure that uses quantifiable hydrological estimates of the future climate and accounts for multiple river basin objectives from stakeholders. The approach is a hybrid approach that applies the updated flood frequency methodology for accounting for climate change and an adaptive management framework for managing uncertainty and multiple basin objectives. The adaptive management framework defines and maintains baseline objectives of existing climate stressors and basin users while designing the primary water infrastructure, in a manner that accounts for nonstationarity and uncertainty. The adaptive management approach allows for regular review and refinement of the application of climate data and adjustments to basin objectives, thereby reducing uncertainty within the data needed for decision-making. This new approach provides a cost-effective way to use climate change projections, is applicable to all basins and projects irrespective of geographic location, size, or basin uses, and has minimal subjective components thereby making it reproducible.
Keywords: climate change; nonstationarity; adaptive management; water infrastructure design; multi-objective decision analysis